Banana mulching, sleeving and nutrient pouch feeding technology - Patel, Tushar Umedbhai (Indian Horticulture, 2020)
A number of factors influence banana production like climate, soil, variety, irrigation and fertilizer management etc. In view of higher productivity of banana as well as efficient use of water and fertilizer with drip irrigation, it is becoming more popular among the farmers’ of South Gujarat. In order to enhance the productivity of banana further, adoption of advance technology, viz. use of good quality planting materials, tissue culture plant, fertigation, mulching, sleeving and nutrient pouch feeding at distal end after de-navelling etc. along with drip irrigation are being advocated to the farmers by the University. Significant benefit was obtained from this model and here is an account of farmer’s journey.